Seepage rate of hydrothermally generated petroleum in East African Rift lakes: An example from Lake Tanganyika. (April 2018) - Oppo, Davide; Hurst, Andrew
Abstract: Synthetic Aperture Radar images provide temporal coverage of the oil seepage recurrence at Cape Kalumba, Lake Tanganyika. In combination with legacy seismic data, it has been possible to reconstruct the geological context that regulates seepage and estimate the oil seepage rates. Oil seepage is along fractures associated with the East Ubwari Faults, which in turn promote an active hydrothermal system that matures very shallow (10's m below the lake floor) oil-prone, less than 25 kyr old source rocks. Temporally consistent oil slick origin points are preferentially aligned E-W and SE-NW, and feed oil slicks on the lake surface. Pervasive seeps activity with significant emission rates, up to 449.39 m 3  y -1, proves the presence of high-quality oil-prone source rocks and an active petroleum system that emits oil to form slicks. Hydrothermally-driven source rock maturation occurring at very shallow depth creates a narrow depth-window for conventional trapping of oil. Elsewhere in the lakes of the East African Rift, where similar hydrothermal systems occur, oil slicks may only be indicative of active petroleum systems without the presence of conventional traps. Highlights: The average annual total seepage rate in the Cape Kalumba seeps is 138.7 m 3 Oil emission from single seeps is consistent with globally-significant provinces. Oil migrates along strata toward lake border faults and seeps in the water column. Rapid generation of unconventional hydrothermal petroleum may occur in rift lakes. The petroleum system generating the oil seeps lacks of accumulation capabilities.